FiLaCTM: The Latest Revolution in Anal Fistula Treatment - A Literature Review of Various Therapeutic Techniques - Sukentro, Tony; Thohir, Ya; Purwoko, Reza Yuridian; Asmail; Karvenio, Berliano (GoAcademica Research & Publishing, 2024)
Anal fistula, an abnormal tunnel anal and rectal’s mucosa to surrounding skin in anus or perianal region, has long been considered a complex clinical challenge. This condition often poses a threat in long-term treatment due to the recurrence high risk and incontinence. In this article, we narratively review a number of scientific literatures regarding new treatment techniques which been employed to address anal fistula in the past five years. We objectively evaluate the pros and cons of each technique according to clinical outcomes, and aim to explore the most effective treatment strategy for anal fistula. To date, surgery remains the primary method used to treat anal fistula. However, there has not yet been a single technique that is simple and capable of fully curing complex anal fistulas. In undertaking surgical treatment, both healing outcomes and the protection of anal function must be comprehensively considered.